2003
DOI: 10.1177/153857440303700601
|View full text |Cite
|
Sign up to set email alerts
|

Adjuncts to Improve Patency of Infrainguinal Prosthetic Bypass Grafts

Abstract: The superiority of autologous venous conduit for infrainguinal arterial bypass has been well documented, especially when the bypass extends below the knee or to the tibial arteries. Nevertheless, when adequate autologous vein is not available, prosthetic bypasses (eg, polytetrafluoroethylene [PTFE] or Dacron) are often used in limb-salvage situations. The inferior long-term patency of these infrainguinal prosthetic bypasses has been documented by a number of studies. One such study reported a prospective multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Although no specific societal recommendations exist in this regard, 27 our findings show that reasonable outcomes may be achieved for less-than-optimal lower extremity bypass grafts for a duration of at least 1 year.…”
Section: Discussionmentioning
confidence: 71%
“…Although no specific societal recommendations exist in this regard, 27 our findings show that reasonable outcomes may be achieved for less-than-optimal lower extremity bypass grafts for a duration of at least 1 year.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, the need for adjunctive procedures at distal anastomotic sites was associated with poorer periop- erative patency rates. 19 In our series, adjunctive distal procedures were used more frequently in patients with poor runoff status, with severe clinical conditions (grade 5 and 6 of Rutherford's classification), and in reinterventions. Median duration of follow-up in our registry was 25.5 months, which is similar to the recent study from Daenens et al 20 Our estimated 36-months survival rate (83%) might seem high, considering the poor clinical condition of our patients.…”
Section: Discussionmentioning
confidence: 98%
“…To increase long-term PTFE graft patency, we added an AV fistula to the PTFE interposition site of the femoral vein. Several techniques can be used to increase prosthetic graft patency, such as vein cuffs, vein patches, and AV fistulae [8]. Richardson et al [9] reported the results of temporary AV fistulae for the management of traumatic venous injuries of the lower extremity in 8 patients, and noninvasive Doppler studies performed in 4 of the 8 patients at 3 to 8 months post-repair revealed no evidence of deep venous obstruction [9].…”
Section: Discussionmentioning
confidence: 99%